Behaviour of Basalt Fiber Reinforced Concrete Filled Mild Steel Tube - A, Arunraj; Kumar J, Ashwin; J, Ajith (International Journal of Engineering and Technology, 2018)
The present study is an attempt to understand the behavior of concrete filled steel tubular column under uniaxial load. A concrete-filled steel tubular (CFST) column is formed by filling a steel tube with concrete. It is well known that concrete- filled steel tubular (CFST) columns are currently being used in the construction of buildings, due to their excellent static and earthquake-resistant properties, such as high strength, high ductility, large energy absorption capacity, bending stiffness etc. The external strengthening of using basalt fiber reinforced concrete material is emerging as a new trend in enhancing the structural performance concrete filled steel tubular members to counteract the drawbacks of the past rehabilitation work. In this project we are going to study about strength of the steel and concrete by doing compression strength, flexural strength, push out and uniaxial compression test. The tests are carried out with the help of universal testing machine. The readings are recorded and graphs are plotted.Â Â